2022
DOI: 10.1038/s41598-022-20222-7
|View full text |Cite
|
Sign up to set email alerts
|

Navigation accuracy and assessability of carbon fiber-reinforced PEEK instrumentation with multimodal intraoperative imaging in spinal oncology

Abstract: Radiolucent carbon-fiber reinforced PEEK (CFRP) implants have helped improve oncological follow-up and radiation therapy. Here, we investigated the performance of 3D intraoperative imaging and navigation systems for instrumentation and precision assessment of CFRP pedicle screws across the thoraco-lumbar spine. Thirty-three patients with spinal tumors underwent navigated CFRP instrumentation with intraoperative CT (iCT), robotic cone-beam CT (rCBCT) or cone-beam CT (CBCT) imaging. Two different navigation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Drawbacks of CF implants include its potential challenging surgery due to its radiolucency. However, recent research has shown CT-guided navigation of pedicle screws is possible for instrumentation and precision assessment across the thoraco-lumbar spine 41 . Besides, long-term postoperative results of CF implants, including the effect of radiation on the properties of CF implants, remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Drawbacks of CF implants include its potential challenging surgery due to its radiolucency. However, recent research has shown CT-guided navigation of pedicle screws is possible for instrumentation and precision assessment across the thoraco-lumbar spine 41 . Besides, long-term postoperative results of CF implants, including the effect of radiation on the properties of CF implants, remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The positioning of the endplates can be clearly determined in 3D imaging as well as 2D X-ray which enables visualization of all crucial elements of the implant and clearly helps to exclude insufficient cage placement. Comparable issues as described for the assessment of CFR PEEK pedicle screw placement on intraoperative imaging were not found [ 7 ]. No case of intraoperative cage revision was required with intraoperative imaging being sufficient in all cases.…”
Section: Discussionmentioning
confidence: 99%